WEB BASED AIR POLLUTION INSTRUMENTATION MONITORING SYSTEM - Ari, Ginaldi; Awaludin, Asif; Suherman, Heri; Latief, Chunaeni; Sinatra, Tiin; Sofiati, Iis (Teknologi Indonesia, 2013)
Air pollution dispersion is not only affected by emission source but also by meteorological factor that is involved. Local meteorological factor will change the air pollution dispersion pattern both in urban area and inanother region. Concavity and valley topographic condition in Bandung city will enable temperature inversion and bring about air fl ow back circulation, causing CO pollutant accumulation. CO is one of the primary pollutants that emits directly from the emission source. It is colorless and odorless gas, posseses longer lifetime which is 30-90 days in the troposphere, and also reduces bodys capability of oxygen absorbance, forming carboxy haemoglobin when being inhaled by human. CO concentration monitoring has been conducted by building and designing CO measurement system equipped with temperature and oxygen monitoring. This integration system consists of sensors (over CO, temperature and oxygen), GPRS modem interface module, sensor interface module, webserver and compilation data system completed with graphical visualization of the CO concentration and surface temperature data every 15 minutes. Analysis on CO concentration trend and observation on surface temperature will become references for the research on local meteorological infl uence toward CO ambient concentration.